The last Mughal : the fall of a dynasty : Delhi, 1857 - Dalrymple, William (New York : Alfred A. Knopf, 2007)
A portrait of Mughal emperor, poet, and mystic Bahadur Shah Zafar II relates the 1857 armed uprising against British rule, the fall of the Mughal capital of Delhi and its subsequent destruction, and Zafar's final days as an exile in Burma.
A chessboard king -- Believers and infidels -- An uneasy equilibrium -- The near approach of the storm -- The sword of the lord of fury -- This day of ruin and riot -- A precarious position -- Blood for blood -- The turn of the tide -- To shoot every soul -- The city of the dead -- The last of the great mughals.
"Originally published in slightly different form in Great Britain by Bloomsbury Publishing, London, in 2006"--T.p. verso.
Includes bibliographical references (p. [503]-512) and index.
Keywords: Muhammad Bahadur Shah -- II, -- King of Delhi, -- 1775-1862.; India -- History -- Sepoy Rebellion, 1857-1858.; Mogul Empire -- History -- 19th century; Delhi (India) -- History -- 19th century